Client satisfaction and quality of health care in a rural medical institute of central Uttar Pradesh - Kumar, Sandip; Jaiswal, Kriti; Jain, Pankaj Kumar; Srivastava, Dhiraj Kumar; Kaushik, Amit; Dixit, Anand Mohan (Indian Journal of Community Health, 2014)
Background: Consumer satisfaction is recognized as an important parameter for assessing the quality of patient care services. Satisfaction regarding the attitude of providers toward these services is expected to affect treatment outcome and prognosis. Out Patient Departments (OPDs) need to monitor the quality of care and patient satisfaction for continuous quality improvement. A major component of quality of health care is patient satisfaction. Present study has been conducted to assess consumer satisfaction with regard to clinical care in the Out Patient Department of Rural Medical Institute of Central Uttar Pradesh. Materials and Methods: The present study was an Outpatient- based cross sectional study conducted in Out Patient Department of UP Rural Institute of Medical Sciences & Research, Saifai, Etawah (UP) between January- June, 2013. A total of 600 patients were selected at random for exit interviews during Out Patients Department hours. Results: The socio-demographic profile of study subjects showed that 57.17% respondents were male and mostly were Hindu (79.67%). A total of 65% were in the age group between 15-59 years. Respondents were patients themselves (86.17%) and accompanying relatives for pediatric patients younger than 15 years old (13.83%). Forty percent of respondents were house wife by occupation. For most of the patients (58.83%) waiting time for consultation was between 15-30 minutes, in 55.17% patients, doctor spent only 5-10 minutes for consultation. A total of 98.67% of the respondents were satisfied with the outpatient department timings.